Analisis Kemiskinan Propinsi Maluku dengan Distribusi Penghasilan Sebagai Variabel Mediasi (Tahun 2005-2017) - Hendri Dony Hahury; Dientje Rumerung; Korneles Sangur (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this paper is to determine the effect of economic growth on poverty directly and indirectly through income distribution. This study uses secondary data of time series data obtained from the Central Statistics Agency of Maluku Province, the year that was the sample in this study between 2005 - 2017. The data analysis model used is path analysis, the analysis method used is descriptive analysis followed by classical assumption tests. and goodness of fit, the analysis tools used by the Eviews and IBM Amos. Hypothesis testing uses multiple regression path analysis techniques. The results of the research and discussion show that there is no influence between economic growth on income distribution, on the contrary, there is an influence between employment opportunities and income distribution. So even though there is economic growth, it does not have an impact on income distribution. Furthermore, it turns out that there is no influence between economic growth on poverty. So the economic growth that occurs does not have an impact on reducing poverty. Conversely, there is an influence between employment opportunities and poverty, which means that changes in employment opportunities will affect the level of poverty. The lack of effect on economic growth and employment opportunities through income distribution on poverty proves that in Maluku poverty indicates that poverty in Maluku is more relative poverty. Poverty that is created is not caused by economic growth and employment opportunities that affect income and consequently creates poverty, but rather due to limited access to various public facilities due to the condition of Maluku which is more dominated by the sea.